Higher adherence to the Dietary Approaches to Stop Hypertension (DASH Diet) is associated with lower greenhouse gases and land use from protein foods - Kling, Nicole R.; Rosentrater, Kurt A.; Lee, Duck-Chul; Brellenthin, Angelique G.; Lanningham-Foster, Lorraine (Frontiers in Sustainable Food Systems, 2023)
Introduction The average American diet is high in red and processed meats which increases one's risk for chronic diseases and requires more land and water to produce and yields greater greenhouse gases (GHG) compared to other protein foods. Reduction of red and processed meat intake, such as seen with the Dietary Approaches to Stop Hypertension (DASH diet), could benefit human and environmental health. Objective The objective of this study is to predict the environmental sustainability of the DASH diet by evaluating the GHG, land use, and water withdrawals from protein foods within the self-selected diets of people who were encouraged to follow the DASH diet. Methods Dietary data was collected from 380 Midwesterners aged 35-70 years old with hypertension using the Automated Self-Administered 24-Hour (ASA 24) Recall System. DASH diet adherence was measured using a nutrient-based DASH score. GHG, land use, and water withdrawals were obtained using Carnegie Mellon University's Economic Input-Output Life Cycle Assessment (eiolca.net) using the Purchaser model (cradle-to-consumer). Multiple linear regressions were used to view associations between individual DASH nutrient scores and environmental impacts of total, animal, and plant protein foods. Results Diets that met DASH diet guidelines, as indicated by higher individual DASH nutrient scores, were associated with less GHG and land use from total and animal protein foods but more GHG and land use from plant-protein foods, with a few exceptions. The pattern was not clear for water withdrawals. Diets with the greatest adherence had around 25–50% lower GHG and land use from total protein foods than diets with the lowest adherence. Changes may be due to decreased consumption of total and animal protein foods, selection of animal protein foods with lower environmental impacts, and increased consumption of plant protein foods. Conclusion Adhering to the DASH diet can promote the consumption of less environmentally demanding protein foods resulting in lower GHG and land use from protein foods. However, claims regarding the sustainability of the entire dietary pattern cannot be determined based off the current study. Regardless, it is evident that environmental impacts should be considered alongside health impacts when selecting, promoting, or recommending a dietary pattern.